Consumers’ understanding and awareness of food irradiation in UiTM Penang / Nor Azureen Rozekhi... [et al.] - Rozekhi, Nor Azureen; Hussin, Shahril; Abdul Rahim Siddiqe, Ashraf Siddik Khan; Bashir, Muhammad ‘Arif Aizat; Abd Majid, Hairul Nizwan (Universiti Teknologi MARA, Negeri Sembilan, 2018)
It has been remarked that food irradiation is an emerging technology with many advantages to consumers. Among the benefits of food irradiation include the destruction of insects, fungi and bacteria that cause food to spoil and causes food borne illnesses in humans. However, there appears to be a lacking in widespread public awareness and understanding of food radiation for human consumption. Therefore, this study is attempting to investigate consumer awareness, attitude, trust and understanding toward food irradiation. A total of 237 respondents participated in the study via self-administered questionnaires. Findings revealed that consumers’ level of awareness towards food irradiation was surprisingly high. On the other hand, level of positive attitude and trust towards irradiated food were accepted. The findings of this study could contribute to the body of knowledge regarding the awareness, knowledge, attitude and trust towards food irradiation among consumers. In addition, it provides information and suggestions for the authorities in governing and imposing rules and regulations on food and beverage operators and handlers in Malaysia.